2009
DOI: 10.1007/s00038-009-0083-1
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of socio-economic inequalities in health among elderly in Greece, Italy and Spain

Abstract: The analysis reconfirms the advantage of high over low socio-economic position for all countries and health indicators and proves education as an important correlate compared to wealth and income among the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 50 publications
2
17
0
1
Order By: Relevance
“…While difficult to make direct comparisons between studies, differences in findings are likely to reflect difference across time and place in underlying social conditions and risk factors, such as obesity, physical inactivity and smoking. With regard to the finding of large inequalities in physical functional limitations, this has been consistently reported among mid age and older people in previous studies [9,15,17,35-37,39,41]. Our finding of substantial inequalities in high psychological distress, particularly among younger people, is also consistent with the weight of evidence, showing higher prevalence of mental health problems among lower socioeconomic groups [42], although inequalities in older people have been less consistently reported [17,35,43].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…While difficult to make direct comparisons between studies, differences in findings are likely to reflect difference across time and place in underlying social conditions and risk factors, such as obesity, physical inactivity and smoking. With regard to the finding of large inequalities in physical functional limitations, this has been consistently reported among mid age and older people in previous studies [9,15,17,35-37,39,41]. Our finding of substantial inequalities in high psychological distress, particularly among younger people, is also consistent with the weight of evidence, showing higher prevalence of mental health problems among lower socioeconomic groups [42], although inequalities in older people have been less consistently reported [17,35,43].…”
Section: Discussionsupporting
confidence: 65%
“…Yet, while many studies on socioeconomic inequalities in the prevalence of chronic conditions include older people, data are usually aggregated for these older participants (often >65 years) e.g. [12-15], (with some exceptions, e.g. [9,16,17]), and there is very limited evidence of inequalities specifically among the oldest old (≥80 years) [9,18].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, even if income and wealth are positively related, income reflects a flow of resources, which are available over a period, while wealth reflects a stock of resources, which are accumulated over a person's lifetime. Among the elderly, levels of income vary much less than levels of wealth, so wealth allows more accurate measurements of SES differences in health and healthcare utilization in this population (Tsimbos 2010, Allin et al 2009). However, this study showed that wealth played a minor role in affecting the examined cognitive tasks of individuals, while education was a significant protective factor to prevent cognitive decline in aging.…”
Section: Discussionmentioning
confidence: 99%
“…Total assets are the sum value of the primary residence net of mortgage, value of the real estate, owned share of own business, owned cars, and the value of financial assets (bank accounts, government and corporate bonds, stocks, mutual funds, individual retirement accounts, and contractual savings for housing and life insurance policies owned by the household) minus financial liabilities. In this study, wealth instead of income was chosen as an economic indicator for elderly people in line with other literature (Tsimbos 2010, Allin et al 2009). …”
mentioning
confidence: 99%
“…7) is being documented. There is now empirical support indicating that the 'healthconomic crisis' is characterized by the following: exponential increases in unemployment, suicidality (Economou, Madianos, Peppou, Patlelakis, & Stefanis, 2013) social exclusion, poverty, homelessness (Giannetou, 2012), increasing socioeconomic inequalities in the older populations (Tsimbos, 2010) and in childhood and adolescence (Anagnostopoulos & Soumaki, 2013), medication shortages (Karamanoli, 2012), violence (Ifanti, Argyriou, Kalofonou, & Kalofonos, 2013) decreases in the use of prevention services and in self-rated health by the elderly and other vulnerable populations (Zarvas et al, 2012) and increases in infectious diseases (Bonovas & Nikolopoulos, 2012;Paraskevis et al, 2011). As a consequence, people's health outcomes and well-being are being put at risk, and the most vulnerable populations are confronting challenges that are often rendered insurmountable (Anagnostopoulos & Soumaki, 2013;Bonovas & Nikolopoulos, 2012;Kondilis et al, 2013).…”
Section: Introductionmentioning
confidence: 98%